Challenges and Facilitators of Health Literacy in Patients with Acute Coronary Syndrome: a Qualitative Study - Sobhi, E.; Moghaddam, H. R.; Habibi Soola, A. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Low health literacy is associated with high prevalence of cardiovascular diseases. Therefore, this study was carried out to identify challenges of health literacy and strategies for its promotion in patients with acute coronary syndrome, using the patients and nurses’ experiences.҆Methodology. Data gathering was done through applying semi-structured interviews with participation of 29 patients and nurses. The informants were selected using purposive sampling method with the maximum variation. Data analysis was done through conventional content analysis and using MAXQDA software. Results. Obstacles and challenges of health literacy in participants were categorized in four themes including irresponsibility, social apathy, perceptual and cognitive problems, and inappropriate distribution of the resources. In addition, possible strategies to promote health literacy were presented in the form of 68 strategies.Conclusions. Given that successful management of many acute or chronic diseases is influenced by patients’ perceptions of health information, providing strategies to people who have difficulty in understanding this information can have a positive effect on health outcomes. Increasing health literacy abilities of patients should be a priority of health system.